Effects of workplace representation on firm-provided further training in Germany - Jens Stegmaier (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2010)
Unions are an important indicator of various measures of firm performance in Anglo-Saxon countries. The same holds for the German analogue of workplace unionism's the works council. Using the IAB Establishment Panel I examine the impact of works councils and shop-floor participation on further training and training intensity. As some studies suggest that the impact of workplace representation varies with firm size, I also test for differences between large and small/medium-sized establish-ments. Pooled logit and count data models are employed to analyze firm's further training activity and training intensity. Because the treatment variables may suffer from endogeneity I also adopt linear and nonlinear instrumental variables techniques. The analysis reveals a positive impact of works councils on firm-provided further training, but provides slightly weaker evidence of firm-size differentials of workplace representation. – – In angelsächsischen Ländern stellen Gewerkschaften einen bedeutsamen Indikator für verschiedene Kennzahlen der betrieblichen Leistungserstellung dar. Das gleiche gilt für die deutsche Form der betrieblichen Interessenvertretung - den Betriebsrat. Unter Verwendung des IAB-Betriebspanels untersuche ich den Einfluss des Betriebsrats und anderen, informelleren Mitarbeitervertretungsformen auf die betriebliche Weiterbildungsaktivität und -intensität. Da aus der Literatur hervorgeht, dass der Einfluss der Mitbestimmung mit der Betriebsgröße variiert, prüfe ich weiter, ob damit Betriebsgrößendifferenziale verbunden sind. Die Weiterbildungsaktivität bzw. -intensität wird anhand von gepoolten Logit- und Zähldaten-Modellen analysiert. Da ein Endogenitätsproblem nicht auszuschließen ist, kommen ferner lineare wie nicht-lineare Instrumentalvariablen-Ansätze zur Verwendung. Die Ergebnisse zeigen, dass der Betriebsrat einen positiven Einfluss auf die betriebliche Weiterbildung hat. Hinsichtlich der betriebsgrößenspezifischen Wirkung ist die Beweisdecke dünner.
Keywords: J53; J24; 330; works council; shop-floor participation; firm-provided further training; Betriebsrat; Mitbestimmung; Betriebliches Bildungsmanagement; Betriebsgröße; Schätzung; Deutschland